ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Survei pada Bus Batik Solo Trans Koridor 2) - Bayu Ari Pambudi, Rahayu Triastity & Sumarno Dwi Saputra (Universitas Slamet Riyadi, 2016)
The purpose of this research was: 1) to analyze the significance of the influence of the quality of service of consumer satisfaction on Batik Solo Trans Bus Corridor 2. 2) to analyze the significance of the influence of the quality of service of customer loyalty on Batik Solo Trans Bus Corridor 2. 3) to analyze the significance of the influence of consumer satisfaction toward customer loyalty on Batik Solo Trans Bus Corridor 2. 4) To analyze the influence of the quality of service of customer loyalty that is mediated by consumer satisfaction on Batik Solo Trans Bus Corridor 2. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of secondary. The population in this research is that consumers never use Batik Solo Trans Bus Transport Corridor 2 in December 2015 until January 2016. Sampling techniques in the research of using accidental sampling, the number of samples that used as many as 100 people. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, linear regression analysis of multiple test, t test, F and the coefficients of determination. The research results obtained conclusions: 1) service quality effect significantly to consumer satisfaction on Batik Solo Trans Bus Corridor 2. 2) quality of service effect significantly to customer loyalty on Batik Solo Trans Bus Corridor 2. 3) influential consumer satisfaction significantly to customer loyalty on Batik Solo Trans Bus Corridor 2. 4) Satisfaction influences the quality of the service of customer loyalty on Batik Solo Trans Bus Corridor 2.Keywords: service quality, customer satisfaction, customer loyalty